2004
DOI: 10.1159/000082753
|View full text |Cite
|
Sign up to set email alerts
|

Functional Long-Term Outcome of a Free Jejunal Transplant Reconstruction following Chemoradiotherapy and Radical Resection for Hypopharyngeal and Proximal Oesophageal Carcinoma

Abstract: Background/Aims: To evaluate the functional outcome of a reconstruction by a free vascularized jejunal transplant combined with a voice prosthesis after chemoradiotherapy and surgery for proximal oesophageal or hypopharyngeal cancer. Methods: Seven patients (6 men, mean age 52 years, range 28–70) with squamous cell cancer in the proximal oesophagus (n = 6) or the hypopharynx received preoperative chemoradiotherapy (40.8 Gy, cisplatinum and 5-FU) followed by a circumferential pharyngolaryngectomy and resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…The method and route used for reconstruction is dependent on the length of defect, an adequate blood supply, a disease-free segment of organ to be used, the functional results, and the surgeon's preference. 10 Some have advocated colonic interposition, 11,12 while others favor a jejunal transfer, either 'free' 13,14 or with a 'supercharged' microanastomosis and pedicle. 15,16 The jejunum as an esophageal conduit was popularized in the 1950s, with Longmire 17 and Androsov 18 pioneering the techniques of microvascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The method and route used for reconstruction is dependent on the length of defect, an adequate blood supply, a disease-free segment of organ to be used, the functional results, and the surgeon's preference. 10 Some have advocated colonic interposition, 11,12 while others favor a jejunal transfer, either 'free' 13,14 or with a 'supercharged' microanastomosis and pedicle. 15,16 The jejunum as an esophageal conduit was popularized in the 1950s, with Longmire 17 and Androsov 18 pioneering the techniques of microvascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the use of prosthetics for voice restoration following TPL . However, most of these were small case series or included various reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the use of prosthetics for voice restoration following TPL. 6,7,[9][10][11] However, most of these were small case series or included various reconstruction methods. Therefore, the features and complications of an indwelling voice prosthesis in patients who undergo TPL with free jejunal reconstruction have not been established in large cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical advantages of a free jejunal graft are easy harvesting, low donor‐site morbidity and good size approximation to the oesophageal lumen. In the past, radical surgery without neoadjuvant treatment resulted in high morbidity and a reduced quality of life, as laryngectomy was frequently performed at the same time11, 12, 18, 21. Nowadays, neoadjuvant therapy is included in the treatment for oesophageal cancer, making limited resection with a free jejunal graft interposition possible and resulting in an improved quality of life with preservation of the larynx and avoidance of persistent dysphagia.…”
Section: Introductionmentioning
confidence: 99%